2020
DOI: 10.3389/fpubh.2020.00484
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Associated With Knowledge and Practice of Helminthic Infection Prevention Among Rural School-Aged Children's Parents in Bangladesh: A Cross-Sectional Study

Abstract: Background: Parasitic infection has become a major public health concern in light of its increasing prevalence in developing countries, particularly in rural settings. Helminthic infections disproportionately affect children, and therefore appropriate parental knowledge and practical approaches to transmission prevention are essential. The objective of this study was to evaluate the level of knowledge and implementation measures aimed at preventing helminthic infection among rural school-aged children's parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…However, these findings were contrary to those of a study carried out in Nigeria [38], in 2011 which reported that less than half of the participants had appropriate knowledge. These findings are also contrary to the results of a study carried out in Bangladesh [39] where a high proportion of caregivers had inadequate knowledge. The difference in these findings could be explained by increase awareness and sensitization campaign efforts made by health authorities through the creation national control programmes, health information from media and awareness by health staff and community health workers.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these findings were contrary to those of a study carried out in Nigeria [38], in 2011 which reported that less than half of the participants had appropriate knowledge. These findings are also contrary to the results of a study carried out in Bangladesh [39] where a high proportion of caregivers had inadequate knowledge. The difference in these findings could be explained by increase awareness and sensitization campaign efforts made by health authorities through the creation national control programmes, health information from media and awareness by health staff and community health workers.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in line with those of a previous study that documented that knowledge is positively and significantly related to behavior [19]. Similar findings have been reported in many previous studies, showing that knowledge mediates the relationship between information and preventive behaviors [31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…Socio-demographic data were collected, including age, sex, monthly family income, academic grade (secondary/higher secondary), relationship status (not in relationship/in a relationship), living together with family (yes/no) and perceived relationship with friends (good/not good). Socioeconomic status (SES) was categorized into three classes based on monthly family income: lower (less than 10000 Bangladeshi Taka [BDT] ≈ < 120 US$), middle (10000–20000 BDT ≈ 120–240 US$), and upper (more than 20000 BDT ≈ > 240 US$) [ 13 , 14 ]. A pilot test was conducted on 30 students to confirm the reliability of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%